2014
DOI: 10.1557/opl.2014.764
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Utilization of Coconut Fibers of the Caribbean

Abstract: In many tropical countries coconut (coir) fiber production is a major source of income for rural communities. The Caribbean has an abundance of coconuts but research into utilizing its by-products is limited. Environmentally friendly coir fibers are natural polymers generally discarded as waste material in this region. Research has shown that coir fiber from other parts of the world has successfully been recycled. This paper therefore investigates the mechanical properties of Caribbean coir fiber for potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…[ 11 ] Mathura et al concluded that the coir fiber is ideal for situations, which require impact toughness due to their high strain at break despite having low‐tensile strength and modulus. [ 12 ] Naveen and Yasaswi concluded that coir could be a potential reinforcement as it helps in increasing both mechanical and dynamic properties of composite. [ 13 ] Mohammed et al reviewed natural fiber composites and concluded from their review that chemical treatments can be used to enhance the mechanical and physical properties of natural fiber‐reinforced polymer matrix composite.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Mathura et al concluded that the coir fiber is ideal for situations, which require impact toughness due to their high strain at break despite having low‐tensile strength and modulus. [ 12 ] Naveen and Yasaswi concluded that coir could be a potential reinforcement as it helps in increasing both mechanical and dynamic properties of composite. [ 13 ] Mohammed et al reviewed natural fiber composites and concluded from their review that chemical treatments can be used to enhance the mechanical and physical properties of natural fiber‐reinforced polymer matrix composite.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main limitations that made it difficult to broaden the industrial use of this polymer was its high cost; for this reason, this polymer was frequently mixed with low cost biodegradable materials [12]. Coir is extracted from coconut husk and can be either white (from green coconuts) or brown (from mature coconuts) [13]. Coconut palm (Cocos nucifera) is grown in many countries throughout the tropics and coir industry is well developed in India and Sri Lanka, but also economically important in countries like Brazil and Indonesia [14].…”
Section: Introductionmentioning
confidence: 99%